IEEE/ASME/ASCE 2008 Joint Rail Conference 2008
DOI: 10.1115/jrc2008-63052
|View full text |Cite
|
Sign up to set email alerts
|

Update on Ongoing Tank Car Crashworthiness Research: Predicted Performance and Fabrication Approach

Abstract: Research is currently underway to develop strategies for maintaining the structural integrity of railroad tank cars carrying hazardous materials during collisions. This research, sponsored by the Federal Railroad Administration (FRA), has focused on four design functions to accomplish this goal: blunting the impact load, absorbing the collision energy, strengthening the commodity tank, and controlling the load path into the tank. Previous papers have been presented outlining the weight and space restrictions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…Figure 5 shows the various stages of assembly for an alternative design. This illustration differs from that shown in the original [3] in two ways. Here only the ends (head) of the conventional tank are reinforced.…”
Section: Preliminary Conceptual Designcontrasting
confidence: 39%
See 3 more Smart Citations
“…Figure 5 shows the various stages of assembly for an alternative design. This illustration differs from that shown in the original [3] in two ways. Here only the ends (head) of the conventional tank are reinforced.…”
Section: Preliminary Conceptual Designcontrasting
confidence: 39%
“…Under these assumptions, the initial evaluations suggested that the desired performance goal could be attained [3]. Considering the generalized head impact scenario, the improved design was shown to absorb about eight times as much energy as the conventional tank.…”
Section: Figure 5: Progression Of Conceptual Design Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…A. Definition of materials ASTM TC-128B steel was selected as the material of the structure because currently most tank cars are currently made with this material [14], whose properties are shown in Table II. A36 structural steel was defined as material of the lugs because according to regulations, these additions must be simulated numerically with this material.…”
Section: B Formulations For Linear Problems Of Elasticitymentioning
confidence: 99%